The memory process : neuroscientific and humanistic perspectives - Nalbantian, Suzanne, 1950-; Matthews, Paul M.; McClelland, James L. (MIT Press, 2011)
The convergence of neuroscience, philosophy, art, music & literature offers valuable new insights into the study of memory.- Resumé vydavatel
Keywords: paměť; memory; elektronické knihy; sborníky; electronic books; papers of several authors